The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1975
DOI: 10.2135/cropsci1975.0011183x001500030025x
|View full text |Cite
|
Sign up to set email alerts
|

Shrunken Endosperm Mutants in Barley1

Abstract: Six spontaneous shrunken endosperm mutants in barley (Hordeum vulgare L.) were identified and described. Five of the mutants (se1 through se5) were inherited as maternal plant monofactorial recessives and one mutant se6 was inherited as a monofactorial recessive expressing xenia. The mutants varied in fertility, seed weight, and seive size assortment. Four mutants were located on chromosome one, one on chromosome three, and one on chromosome six, by using translocation breakpoints as markers. Mutants similar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
14
0

Year Published

1978
1978
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Rather than reviewing every mutation, we will discuss selected mutations that in our opinion provide crucial insight. There are a number of publications that contain a wealth of information about mutations affecting endosperm development in cereals (Jarvi and Eslick, 1975;Nelson, 1980;Neuffer and Sheridan, 1980;Satoh and Omura, 1981;Bosnes et al, 1987;Kowles et al, 1992;Scanlon et al, 1994;Kurata et al, 2005;Dolfini et al, 2007).…”
mentioning
confidence: 99%
“…Rather than reviewing every mutation, we will discuss selected mutations that in our opinion provide crucial insight. There are a number of publications that contain a wealth of information about mutations affecting endosperm development in cereals (Jarvi and Eslick, 1975;Nelson, 1980;Neuffer and Sheridan, 1980;Satoh and Omura, 1981;Bosnes et al, 1987;Kowles et al, 1992;Scanlon et al, 1994;Kurata et al, 2005;Dolfini et al, 2007).…”
mentioning
confidence: 99%
“…The segl character is inherited as a maternal plant monofactorial recessive gene not expressing xenia (5), and therefore segl plants produce shrunken seeds regardless of pollen source, and no segregation of kernels occurs within plants. This inheritance pattern is not typical of endosperm mutations in which sugar metabolism or starch synthesis enzymes are affected.…”
Section: Discussionmentioning
confidence: 99%
“…One approach to the problem has been to examine a series of barley (Hordeum vulgare L.) shrunken endosperm mutants which are inherited as maternal plant monofactorial recessives and do not express xenia (5). We investigated segl, a mutant of the cultivar Betzes, which produces seed with 35 to 55% of normal dry weight (2).…”
mentioning
confidence: 99%
“…Until late last year, when Ray et al (1996) showed that normal embryonic pattern formation in Arabidopsis requires the maternal expression of the SHORT INTEGUMENT gene, the only direct genetic evidence that the sporophytic tissues of the ovule may be involved in controlling either embryo or endosperm development was an isolated report of maternal-effect mutations that cause a shrunken endosperm phenotype in barley (Jarvi and Eslick, 1975). Colombo et al have extended our understanding of the role of the sporophytic tissues of the ovule during seed development.…”
mentioning
confidence: 99%